Association of IL-8 and CXCR2 with AST/ALT Ratio in Liver Abnormalities Screening during Oxidative Stress Injury Caused by VCM - Yiwen Dong; Xingang Wang; Weijiang Hu; Xin Wang; Hongying Bian; Wencui Zhang; null Feng Han; Ning Kang; Lin Zhang; Meng Ye (Journal of Toxicology)
Liver impairment caused by VCM has been linked to irreversible damage such as fibrosis, necrosis, hepatocellular carcinoma, and liver angiosarcoma. However, the ability to detect abnormalities during initial phase have not been achieved so far. Thus, this study aimed to investigate the effect of interleukin 8 (IL-8) and C-X-C chemokines 2 (CXCR2) on screening for a VCM-exposed group (n = 227) from a PVC manufacturing factory compared to a control group (n = 110) in Tianjin City in 2020 with influence factors evaluation. Ambient concentrations of VCM and health archives from 2012 to 2018 were collected for establishing the dose-effect trend. A cross-sectional survey in 2020 was performed to measure TDGA, IL-8, CXCR2, 8-OHdG, SOD, GPX, CAT, MDA, and ROS levels. Results indicated a continuous increased incidence on liver abnormalities despite a fluctuated downward trend in cumulative time-weighted average (CTWA) VCM concentrations over the years. ALT, AST, and AST/ALT ratio all contributed to liver abnormalities that contained fatty liver, liver calcification, and liver cysts, IL-8 and CXCR2 correlated with each other strongly and showed significant associations with oxidative stress markers, even AST/ALT ratio. IL-8 (>1547 µg/m3) or CXCR2 (<139 µg/m3) influenced the AST/ALT ratio through reciprocal interactions under oxidative stress injury, CXCR2 (>222 µg/m3), working years of 21 to 30 (a) and 11 to 20 (a), TDGA (>1.52 mg/L), alcohol consumption, smoking habit, and a less sleeping duration of <4 h per day would also be potential factors affecting the AST/ALT ratio. In conclusion (1) even with decreased VCM concentrations in PVC manufacturing factories liver abnormalities that contained fatty liver, liver calcification, and liver cysts could still occur due to oxidative stress injury with involvement of IL-8 and CXCR2. The status of protective measure and appropriate mask types also play a role; (2) the AST/ALT ratio could be a specific indicator for detecting abnormalities when combined with liver B ultrasonography results before impairment altered from bad to worse; and (3) factors such as definite medication history, fully broken protective facilities, alcohol consumption, less sleeping duration, inappropriate mask types, and longer working years could also influence AST/ALT ratio alterations through complex interactions.